TINJAUAN YURIDIS PENGELOLAAN USAHA TAMBANG PASIR BERDASARKAN UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 3 TAHUN 2020 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 4 TAHUN 2009 TENTANG PERTAMBANGAN MINERAL DAN BATUBARA - Firmansyah, Sugiarto (Madani Legal Review, 2020)
This study aims to determine how a juridical review of the management of a sand mining business based on Law of the Republic of Indonesia Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining and whether the form of government supervision in managing sand mining business is based on the Law Law of the Republic of Indonesia Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining, is considered effective. This study uses a normative method by examining legal documents and other papers and their application to legal events through data collection techniques by means of literature studies and data analysis techniques used are descriptive qualitative. Based on the data analysis carried out, the juridical review of the management of the sand mining business is not in accordance with the application of the existing reality in the field where production operations that have a mining business license, but the determination of the sand mining business license area is not in accordance with the location of its designation. The form of government supervision in managing the sand mining business is deemed ineffective, causing problems regarding the mining business license area and mining business license, so it is necessary to increase coordination between the form of internal control supervision and the form ofcontrol supervision external